USING THE N-15 METHOD TO DETERMINE N-SOIL, N-GREEN MANURE, AND N-UREA AVAILABILITY AFTER SIX SEASONS IN AN ALLEY CROPPING SYSTEM - Sisworo, Elsje L.; Haryanto; Citraresmini, Ania (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2013)
Nitrogen (N) is the most important nutrient for crop growth and production. This study was conducted to determine whether in each of six seasons and after these seasons the N-soil, N-green manure, N-green manure + urea, and N-urea is still available for crops. Upland rice and corn were planted successively for six seasons. In each season upland rice and corn were planted and applied with N-fertilizers at rate of: control (0N), N1 (100% green manure), N2 (50% green manure + 50% urea), N3 (100% urea). N-15 labelled urea was added at each season to determine the A-value of the crops. In each seasons it was shown that crops used N-soil as well as N-fertilizer. With the increase of the availability of N-fertilizers the use of N-soil decrease and so could preserve N-soil. With preservation of N-soil it could be assumed that soil quality has increased. The N-15 method could be used to determine the availability at each fertilizer rate’s in each season and at the end of the sixth season.